Assessment of scientific and technical projects of priority directions of development based on the criterion of use value - L. F. Zakharova; S. V. Novikov (Управление)
The article deals with the problems of efficiency of evaluation and selection of scientific and technical projects of priority development directions of the national economy for their financing from the federal budget of the Russian Federation. The improvement of existing competitive procedures is proposed using the developed tool for the evaluation of the final result - the aggregate product of a scientific and technical project, considered as a set of all possible product outputs that have utility in various sectors of the economy, including as conversion solutions. For targeted use of the state’s investment resources in strategically effective areas, when selecting projects, it is proposed to link them to allocatively grouped sectors of the economy which consider the sectors of the strategic core as well as sectors of the I and II kind. The indicator of the aggregate product of the project is estimated by its use value as an additive form of convolution of the partial indicators of technical quality of all possible project outputs using the evaluation of their marketing support in possible sales markets. The article deals with the organizational and procedural schemes of proposed solutions for improving the evaluation of scientific and technical projects, as well as the economic and mathematical tools for ranking the priority directions for the development of the Russian economy for the financing of scientific and technical projects from the state budget. A polyciritorial evaluation of the final result of the project and use of the aggregate product as a resultant estimator of the use-value criterion makes it possible to objectify complex procedures for competitive selection of large-scale projects, increase their economic performance, as confirmed by the approbation studies on the example of the project for the creation and production of multifunctional on-board radar equipment.